Artificial Intelligence Software and Its Implications for Firms - (:unkn) unknown (My University, 2022)
The Internet of Things (IoT) industry has been described as the third digital revolution, following advances in the traditional Internet and mobile Internet channels. One of the most widely adopted IoT innovations is the smart speaker (e.g., Amazon Echo, Google Home), which provides users with access to voice assistants (e.g., Amazon Alexa, Google Assistant). Voice assistants employ Artificial Intelligence (AI) software to have natural-language voice interaction with users and can perform a variety of tasks such as setting an alarm or timer, playing music, and controlling other smart objects. With the goal of expanding both the quantity and types of tasks available, Amazon and Google allow independent developers to create their own AI software (e.g., Amazon Skills, Google Actions) to provide more value to users. Many firms have begun to develop this software; for example, Whirlpool allows users to start a load of laundry on their washing machines, Chipotle allows customers to re-order their favorite meals, and Pandora allows users to search for and play music, by simply issuing hands-free voice commands to their smart speakers. While such software clearly provides benefits to consumers, no research has evaluated the potential value perceived by investors. As investors’ evaluations of firms consider the expected revenue and costs involved in designing, creating, and marketing innovations such as smart speaker AI, this dissertation adopts the event study methodology to examine investor response as manifested through stock market behavior. It aims to uncover the overall impact that smart speaker AI has had on firm value, and whether certain AI-, firm-, or industry-specific characteristics moderate this impact in a positive or negative way.
Keywords: event study; firm value; Internet of Things; smart speaker; voice assistant software